2022
DOI: 10.1055/s-0041-1741080
|View full text |Cite
|
Sign up to set email alerts
|

Why Peritoneal Dialysis is Underutilized in the United States: A Review of Inequities

Abstract: Given a choice, most patients with end-stage renal disease prefer home dialysis over in-center hemodialysis (HD). Peritoneal dialysis (PD) is a home dialysis method and offers benefits such as absence of central venous access and therefore preservation of veins, low cost, and decreased time per dialysis session, as well as convenience. Survival rate for patients on PD has increased to levels comparable to in-center HD. Despite endorsement by leaders in the medical field, professional societies, and those in go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As PD demand increases with the implementation of the ESKD Treatment Choices and Kidney Care Choices models in the United States, 16 it is critical to identify limitations to the United States' ability to facilitate the use of PD. Patients who are subjected to follow-up procedures and operators who are faced with nonfunctional catheters may lose interest in pursuing PD, 9 or clinical conditions may eventually require some patients to start hemodialysis before a functional PD catheter becomes available. 17 Theoretically, interventional nephrologists and radiologists may be more readily available to insert PD catheters given that these procedures do not require an operating room and anesthesia team to be available, and an approach that does not require anesthesia may be preferred for patients with multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As PD demand increases with the implementation of the ESKD Treatment Choices and Kidney Care Choices models in the United States, 16 it is critical to identify limitations to the United States' ability to facilitate the use of PD. Patients who are subjected to follow-up procedures and operators who are faced with nonfunctional catheters may lose interest in pursuing PD, 9 or clinical conditions may eventually require some patients to start hemodialysis before a functional PD catheter becomes available. 17 Theoretically, interventional nephrologists and radiologists may be more readily available to insert PD catheters given that these procedures do not require an operating room and anesthesia team to be available, and an approach that does not require anesthesia may be preferred for patients with multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…18 In other nations where PD use is highly prevalent, interventional nephrologists have become the primary operators who place PD catheters. 9,[19][20][21] A previous trial demonstrated that catheter complication-free survival was higher (42.5%) in those receiving catheter implantation with radiology as opposed to general surgeons (18.1%). 22 Other studies have varied in their findings, with some showing that exit site leak was more common in catheters placed percutaneously as opposed to a surgical approach and other studies showing low complication rates with radiology-placed percutaneous catheters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Although most (approximately 85%) patients requiring KRT qualify for PD, uptake in the United States remains low. 3 As of 2020, 64,406 patients with prevalent kidney failure were receiving PD (12% of all dialysis among patients with kidney failure). 4 Changes in health care policies have contributed to recent increases in home-based dialysis, including PD utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these successes in improving catheter outcomes and reducing technique failure, the utilisation of PD in Japan has remained flat over the past decade, 1,27,28 implicating the influence of other globally recognised government, physician and patient barriers that must be addressed to effectively grow PD. [29][30][31] On a final note, throughout the manuscript, Sakurada and company used mixed terminologies of catheter patency failure and survival and technique failure and survival, but they were clear in how the terms were applied. However, it has been suggested by the SONG-PD (Standardized Outcomes in Nephrology-Peritoneal Dialysis) consensus workshop to use positively framed terminology, therefore, survival instead of failure, in reporting patient outcomes to convey a more appropriate perception of PD therapy.…”
mentioning
confidence: 99%